(untitled) (Journal of history, 2023)
The article describes the socio-philosophical views of the prominent figure and thinker of China Kang Yuwei during the period of political renewal. In addition, the article presents the intellectual achievements and utopian views of Kang Yuwei, who considered himself the founder of a new political direction. Accordingly, the experience of Western civilization occupies a significant place in his philosophical and historical teaching. Kang Youwei’s Datong Shu says that seeing the disintegration of the society of the countries of the world, it is necessary to prevent it, and it is necessary to unite the society. Kang Yuwei’s books occupy a worthy place in the history of Chinese social and political thought. Based on the synthesis of traditional Chinese thought and Western ideas, he created a unique theoretical heritage that influenced the life of Chinese society. Kang Yuwei examined the forms of management and the basic principles of service in a historical aspect. Based on the experience of Western countries and the unique traditional thinking of China, he proposed a number of improvements to the state, in particular, the reform path, the universal principle, and the universal law. The article is devoted to these aspects. In addition, the article also revealed that the foundations of some of the views of Kang Yuwei are actively used in the modern political life of China. Key words: Kang Yuwei, utopia, philosophy, reform, Datong, modernization, Confucianism, political position, Western experience.